Analyzing the long-term impact of post-disaster relocation and implications for disaster recovery policy. (15th February 2022) - Tan, Shin Bin; Waters, Mary C.; Arcaya, Mariana C.
Abstract: Formulating disaster responses that mitigate social inequalities is crucial because disasters disproportionately harm marginalized communities. This study seeks to inform more equitable post-disaster policies by examining how post-disaster residential outcomes relate to subsequent income and health outcomes among a sample of Hurricane Katrina survivors. Analyzing pre-hurricane survey data, three waves of survey data over 12–15 years post-disaster for 385 low-income women, as well as qualitative data from a subset of participants, we show that durable residence in counties previously shown to promote greater intergenerational socioeconomic advancement predicts higher income, but not better mental or self-rated health. Statistical control for prospectively collected, pre-disaster confounders, coupled with qualitative insights, suggest causal relationships between county-level opportunity and income. We further find that persistence in high opportunity counties was driven by family obligations, relationship changes, or access to job opportunities, not differences in individual priorities. Disaster policy should better support displaced survivors' ability to access high opportunity areas.